Описание эволенты и ее свойств - Павлов, А. И.; Павлов, В. А.; Колиснык, А. (НТУ "ХПИ", 2012)
Записано дифференциальное уравнение эволенты, выполнено описание и определены свойства эволенты, которая является линией зацепления в эволютной зубчатой передаче

The evolent’s differential equation is written down, the description is lead and properties of evolent, which serves as a line of action in a tooth gearing, are certain
Keywords: линия зацепления; зубчатая передача; полюс передачи; радиус кривизны; evolent’s differential equation; description; evolent; line of action